2020
DOI: 10.3390/app11010254
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Classification Method for MSI Status Prediction Based on Deep Learning Approach

Abstract: Colorectal cancer is one of the most common cancers with a high mortality rate. The determination of microsatellite instability (MSI) status in resected cancer tissue is vital because it helps diagnose the related disease and determine the relevant treatment. This paper presents a two-stage classification method for predicting the MSI status based on a deep learning approach. The proposed pipeline includes the serial connection of the segmentation network and the classification network. In the first stage, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…6,7 Since 2019, >10 studies have shown that MSI/dMMR status can be detected from digitized pathology slides stained with hematoxylin and eosin (H&E). [8][9][10][11][12][13][14][15][16][17] The key technology that enables this is deep learning (DL), an artificial intelligence (AI) method. Such AI-based systems for detection of MSI/ dMMR status from routine histopathology slides are also in the focus of commercial interest, as evident by a US patent application of this technology (#16/412362 filed on 2019-11-14 by Tempus Labs).…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Since 2019, >10 studies have shown that MSI/dMMR status can be detected from digitized pathology slides stained with hematoxylin and eosin (H&E). [8][9][10][11][12][13][14][15][16][17] The key technology that enables this is deep learning (DL), an artificial intelligence (AI) method. Such AI-based systems for detection of MSI/ dMMR status from routine histopathology slides are also in the focus of commercial interest, as evident by a US patent application of this technology (#16/412362 filed on 2019-11-14 by Tempus Labs).…”
Section: Introductionmentioning
confidence: 99%
“…Another study conducted in 2020 by Lee et al [61] developed a two-stage DL-based classification pipeline for predicting MSI status in CRC patients. In the two-stage process, the first stage was responsible for segmenting the tumor area into two types of tissue (MSI-H and MSI-L).…”
Section: Msi Detectionmentioning
confidence: 99%
“…To aggregate the patch-wise outcomes, other decision procedures were applied; nevertheless, they all showed similar results, and none of them outperformed the separate results. The researcher increased the performance of patch-based CNNs by combining the patch-wise results with a support vector machine (SVM) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%